Colección y presentación de ropa casual femenina: inspirada en rosas ecuatorianas, primavera-verano 2023 - Calderón Sánchez, Judith Dolores (2023)
Fashion is one of the most important sources of entrepreneurship in Ecuador, since in addition to its economic value, it contributes to boosting the local economy and its capacity to generate employment. For several years, there has been talk of sustainable fashion or slow fashion as one of the most innovative alternatives in the textile industry compatible with environmental conservation, care of the environment, tourism promotion and the welfare of societies. The objective of the project was to design a collection of women's casual clothing, taking Ecuadorian roses as a source of inspiration and based on a technical and creative approach. To achieve these goals, a theoretical, descriptive and practical study was conducted, highlighting the history of fashion, current trends and their influence on daily life; in addition, on a methodological approach "action research" preferences, needs, requirements and tastes of women in women's clothing were identified with Ecuadorian roses, which have been awarded in recent years worldwide, taking into consideration that they are part of our culture. Finally, we proposed a collection that presents different types and colors of roses produced in our country, combined with current fashion trends and using materials such as fabrics, accessories, in various colors and shapes